Correlation of Serum Albumin Level to Lung Ultrasound Score and Its Role as Predictors of Outcome in Acute Respiratory Distress Syndrome Patients: A Prospective Observational Study - Souvik Chaudhuri; Sagar S. Maddani; Shwethapriya Rao; Sirish Gauni; N. R. Arjun; Pratibha Todur; Nitin Gupta (Critical Care Research and Practice)
Background. There is ambiguity in the literature regarding hypoalbuminemia as a cause of extravascular lung water and acute respiratory distress syndrome (ARDS) outcomes. The aim of the study was to determine if low serum albumin on admission leads to lung deaeration and higher lung ultrasound score (LUSS) in ARDS patients. Patients and Methods. It was a prospective observational study in which 110 ARDS patients aged between 18 and 70 years were recruited. Serum albumin level and lung ultrasound score were assessed on the day of ICU admission. Length of ICU stay and hospital mortality were recorded. Results. The mean and standard deviation of serum albumin level in mild, moderate, and severe ARDS was 2.92 ± 0.65 g/dL, 2.91 ± 0.77 g/dL, and 3.21 ± 0.85 g/dL, respectively. Albumin level was not correlated to the global LUSS (Pearson correlation r −0.006, p=0.949) and basal LUSS (r −0.066, p=0.513). The cut-off value of albumin for predicting a prolonged length of ICU stay (≥10 days) in ARDS patients was <3.25 g/dL with AUC 0.623, p<0.05, sensitivity of 86.67%, specificity of 45.45%, and 95% confidence interval (CI) [0.513–0.732], and on multivariate analysis it increased the odds of prolonged ICU stay by 8.9 times (Hosmer and Lemeshow p value 0.810, 95% CI [2.760–28.72]). Serum albumin at admission was not a predictor of mortality. LUSS on the day of admission was not useful to predict either a prolonged length of ICU stay or mortality. Basal LUSS contributed about 56% of the global LUSS in mild and moderate ARDS, and 53% in severe ARDS. Conclusion. Serum albumin level was unrelated to LUSS on admission in ARDS patients. Albumin level <3.25 g/dL increased the chances of a prolonged length of ICU stay (≥10 days) but was not associated with an increase in mortality. LUSS on the day of admission could not predict either a prolonged length of ICU stay or mortality. This trial is registered with CTRI/2019/11/021857.